Impact of small and medium scale enterprises (SMEs) in promoting sustainable livelihoods for the youths in Bindura urban - Chigudu, Clarette (Midlands State University, 2017)
In Zimbabwe, the unemployment rate has grown to high levels prompting the youths to resort to the informal sector through SMES as a means of livelihood. This study sought to assess the impact of SMEs in promoting sustainable livelihoods for the youths in Bindura Urban. The mixed research methodology was employed. The study revealed that there are various opportunities such as income, enterprenual skills exchange and low cost labour production that could promote sustainable livelihoods for the youths. It also revealed major barriers to growth of operations which included among others, technology, poor infrastructure, inaccessibility of financial capital, market competition and affordability of registration and operating licenses. The implications are that such barriers would defeat the purpose for which the SMES where set to achieve, that is, reduce the effects of unemployment and promoting sustainable livelihoods. The study provided possible solutions which may be adopted. These include improving loan accessibility through removal of bottlenecks and restructuring of loan requirements by SEDCO and banks, affordable registration fees, a reduction in tariffs for the acquisition of operating licenses, enlargement of market share for the SMEs, expansion of operating premises for SMEs by the responsible authority and government sponsored collateral security for the SMEs. The study recommended further research in other provincial urban centers as the findings may not be used to generalise the situation obtaining in other nine provinces of the country.